IS INTERACTION JUST A DYNAMICAL PROCESS? - Mihai-Alexandru PETRIȘOR (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
In this article I argue for a pluralistic vision of interaction and social cognition in general: we should imagine the landscape of types of interactions as a line segment whose ends represent radical positions (purely inferentialist or purely simulationist theories on one end and radical embodied cognition on the other) on which different types of interactions fall. The closer to any extreme a particular type is, then the more likely it is to be better explained by the theory the extreme point represents. In order to delineate the controversy that stems from different conceptualizations of the same phenomenon and to articulate my position, I criticize Gallagher’s radical claims of embodied cognition as constituting social interaction. The main point that I make regarding his theory is that, even though it provides a satisfactory explanation for types that correspond to motor-perceptual processes, it only manages to metaphorically describe cases of interaction that involve articulated language use and, generally, semantically charged actions. Given that a serious researcher should be interested in accurate predictions or descriptions, it follows that Gallagher’s account is not all-encompassing, and, given the many virtues of other theories, we should adopt a pluralistic point-of-view.